1983
DOI: 10.1159/000158461
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Mesenteric Arteries from Spontaneously Hypertensive Rats

Abstract: Morphometric measurements at the electron microscope level were carried out on three categories of mesenteric arteries representing elastic (superior mesenteric), muscular and arteriolar vessels, from 10- to 12-week-old spontaneously hypertensive rats (SHR) and age-matched Wistar-Kyoto normotensive rats (WKY). Changes were observed only in muscular and arteriolar vessels of SHR, mainly as thickening of the vessel wall due to hypertrophy of the media. In muscular arteries, hypertrophy of the endothelial cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 16 publications
2
52
1
1
Order By: Relevance
“…9 '" Lombard et al 9 also found the greatest dilation in the region of the third-order (A3) arterioles (which are close to the transverse arterioles in our terminology) and attributed the effect to a higher neural transmission and more vigorous responses to oxygen. These observations are compatible with the greater density of nerve plexes in arterioles of SHR 20 and an elevated central sympathetic nerve activity. 21 The fact that the degree of vascular tone varies considerably along individual pathways in the arterioles may suggest that such an elevated nerve activity is not transmitted uniformly along the arteriolar tree.…”
Section: Previous Studiessupporting
confidence: 85%
“…9 '" Lombard et al 9 also found the greatest dilation in the region of the third-order (A3) arterioles (which are close to the transverse arterioles in our terminology) and attributed the effect to a higher neural transmission and more vigorous responses to oxygen. These observations are compatible with the greater density of nerve plexes in arterioles of SHR 20 and an elevated central sympathetic nerve activity. 21 The fact that the degree of vascular tone varies considerably along individual pathways in the arterioles may suggest that such an elevated nerve activity is not transmitted uniformly along the arteriolar tree.…”
Section: Previous Studiessupporting
confidence: 85%
“…25 " 28 Several authors have suggested that smooth muscle cell hypertrophy may be a primary abnormality preceding the development of hypertension. Moreover, in SHRs the increase in stiffness of the arterial wall could participate in hemodynamic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…32 In these vessels, increase in medial wall size is mainly due to hyperplasia of the smooth muscle cells. 33 As discussed above, angiotensin II is known to induce hypertrophy and not hyperplasia of vascular smooth muscle cells. It is also unlikely that prevention of vascular changes in this type of artery was secondary to the prevention of hypertension by captopril because long-term treatment of SHR with vasodilators, although it normalized the blood pressure, was not sufficient to alter the vessel wall dimensions in the renal 20 and mesenteric 34 vascular beds.…”
mentioning
confidence: 96%